Full-Day School Complexity: A Review On Education Sociology Context - Slamet Riyadi; Sigit Apriyanto; Rifai Abun; Andi Warisno; An An Andari; Adelina Anum (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
Full-day school is not the latest issue in Indonesia. Many countries have implemented this system in the world of education, one of which is Indonesia. However, this issue is heating up in Indonesia due to the demands for change, namely the increasingly uncomfortable social environment for children's development. On the other hand, parents rarely accompany their children at home because they work all day long. But, then, is there still a comfortable environment for our children? This study presents a literature review with primary data on articles, magazines, reports, and theories. This study aims to provide an overview of the complexity of FDS from the sociology of education perspective. That the school as a learning organization turned out to be the best institution in fortifying children from the negative influence of an increasingly unfriendly social environment.Â